INTERACTIVE MULTIMEDIA AND MOBILE APPLICATION FOR LANGUAGE LEARNING (MALL) VIEWED FROM MOTIVATION - Andhi Dwi Nugroho (Universitas Sarjanawiyata Tamansiswa, 2019)
The study aims at providing the empirical and theoritical evidence for Â the effect of multimedia and motivation on speaking skills. The quassi experimental study involved 40 students under investigation, determined randomly through multistage random sampling technique. The results of the research indicate that there is an interaction effect between multimedia and motivation on the speaking skills; there is no significant difference in the speaking skills between the group of students who learn using Interactive Multimedia and those who learn using Mobile Assisted Language Learning (MALL); the students with high motivation have better speaking skills than those with low motivation; the students with high motivation who learn using Interactive Multimedia have better speaking skills than those who learn using MALL; and the students with low motivation who learn using MALL have better speaking skills than those who learn using Interactive Multimedia.